A Versatile and Open-Source Rapid LED Switching System for One-Photon Imaging and Photo-Activation - Battefeld, Arne; Popovic, Marko A.; van der Werf, Dirk; Kole, Maarten H. P. (Frontiers in Cellular Neuroscience, 2019)
Combining fluorescence and transmitted light sources for microscopy is an invaluable method in cellular neuroscience to probe the molecular and cellular mechanisms of cells. This approach enables the targeted recording from fluorescent reporter protein expressing neurons or glial cells in brain slices and fluorescence-assisted electrophysiological recordings from subcellular structures. However, the existing tools to mix multiple light sources in one-photon microscopy are limited. Here, we present the development of several microcontroller devices that provide temporal and intensity control of light emitting diodes (LEDs) for computer controlled microscopy illumination. We interfaced one microcontroller with μManager for rapid and dynamic overlay of transmitted and fluorescent images. Moreover, on the basis of this illumination system we implemented an electronic circuit to combine two pulsed LED light sources for fast (up to 1 kHz) ratiometric calcium (Ca2+) imaging. This microcontroller enabled the calibration of intracellular Ca2+ concentration and furthermore the combination of Ca2+ imaging with optogenetic activation. The devices are based on affordable components and open-source hardware and software. Integration into existing bright-field microscope systems will take ∼1 day. The microcontroller based LED imaging substantially advances conventional illumination methods by limiting light exposure and adding versatility and speed.